The Insertion of Archaisms in the 1884 Dictionary of the Royal Spanish Academy (12th ed.) - Jiménez Ríos, Enrique (2023)
Archaisms have always been present in the Dictionary of the Royal Spanish Academy and efforts have been made to preserve and incorporate them. The twelfth edition stands out for its abundant increase in these words to make up for the lack of a specific dictionary of archaisms. Those that were included were mostly formal variants of words in use and they had two characteristics: they were documented for the first time in this edition of the dictionary (others that had appeared before and later removed were reintegrated) and they are preserved even in the latest edition. This occurred at a time when the rehabilitation of archaisms was being promoted as a way to preserve tradition, promote proper language use, and counteract neologisms and loan words.